2019
DOI: 10.3904/kjim.2017.287
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of high resolution computed tomography findings of cystic fibrosis

Abstract: Monitoring of pulmonary physiology is fundamental to the clinical management of patients with Cystic Fibrosis. The current standard clinical practise uses spirometry to assess lung function which delivers a clinically relevant functional readout of total lung function, however does not supply any visible or localised information. High Resolution Computed Tomography (HRCT) is a well-established current 'gold standard' method for monitoring lung anatomical changes in Cystic Fibrosis patients. HRCT provides excel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 84 publications
1
5
0
Order By: Relevance
“…In the present study, there was a significant association between positive results of sputum culture and Bhalla scoring of HRCT findings in children aged 14–16 years (P<0.05). In accordance with our results, Sasihuseyinoglu et al and Robinson et al reported significant relationship between the Bhalla score and bacterial growth in the sputum cultures of children with CF ( 27 , 28 ). On the other hand, Thomas et al didn’t find any significant difference between colonization with P. aeruginosa and S. aureus regarding lung structural changes detected by HRCT, which might be attributed to the relatively small study population and using a different HRCT scoring system ( 15 ).…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, there was a significant association between positive results of sputum culture and Bhalla scoring of HRCT findings in children aged 14–16 years (P<0.05). In accordance with our results, Sasihuseyinoglu et al and Robinson et al reported significant relationship between the Bhalla score and bacterial growth in the sputum cultures of children with CF ( 27 , 28 ). On the other hand, Thomas et al didn’t find any significant difference between colonization with P. aeruginosa and S. aureus regarding lung structural changes detected by HRCT, which might be attributed to the relatively small study population and using a different HRCT scoring system ( 15 ).…”
Section: Discussionsupporting
confidence: 93%
“…Despite many specialist centres using CR as the imaging technique of choice in infants and preschool children, CT shows higher sensitivity in detecting early abnormalities in both symptomatic and asymptomatic CF patients [5,10,12,53,54,[60][61][62][63]. Therefore, using CR in the early post-screening phase seems to be of limited value, with CT being a more efficient way of detecting early disease and monitoring disease progression [10,13,29,50].…”
Section: First Diagnosismentioning
confidence: 99%
“…Spirometry was also used in South American, Turkish and South African children to monitor lung function in cystic fibrosis ( 59 ), and showed good correlation between CT scan Bhalla score and FEV 1 , FVC, FEF 25−75 ( 60 ).…”
Section: Resultsmentioning
confidence: 99%